ANALISIS PERENCANAAN POLA PENANGANAN PERMUKIMAN KUMUH DI KAWASAN SINDULANG SATU, KECAMATAN TUMINTING, KOTA MANADO - Deysi ., Kaseke; Carolina B.D. Pakasi; Charles R. Ngangi (AGRI-SOSIOEKONOMI, 2017)
This study aims to (1) identify the level of untidiness of setllement area in Sindulang Satu Urban Village based on identification of slum conditions (physical), other considerations and legality of land at the site, (2) analyze the pattern of handling the slums and choose the appropriate pattern to be applied to the region. Region slums in the city of Manado North Sulawesi selected as the study area. Limitation of the study area is determined on a region-located strategically Sindulang One area that affects the tourism sector as well as residential typology which is a blend of rolling hills and waterfront settlements (DAS Tondano) and the beach (Boulevard Phase II). The research was conducted for 2 (two) months from the month of January 2017 to February 2017. Methods of data collection is done by the method of field research (Field Research Methods) as well as with library research methods (Library Research Methode). The data used in this research is the primary data collected and processed its own form of existing data found in the object of research is the identification of space utilization, status of ownership of land and buildings, state of the infrastructure and facilities of existing settlements. In addition, also used secondary data is data obtained from other parties or data that are processed or published by various government agencies (Kotaku. 2016). The variables used in this study is the data on the observation of research sites, including the identification of the condition of untidiness / physical, identification of other considerations and identification of the legality of the land, as follows: (1) The condition of the building, (2) The condition of roads, with criteria ie the coverage of the environment and the quality of the road surface environment, (3) the condition of water supply, (4) the condition of drainage environment, (5) Condition wastewater management, (6) Conditions waste management, (7) the condition of fire protection, (8) another consideration, (9) The legality of land. The analysis was performed with regard to the object of analysis and interpretation of the data description of the physical condition, other considerations and the legality of land obtained in the field / location of research and literature review, then associated with a pattern appropriate treatment to be applied to an area of research. The analysis was performed using analysis techniques Formula Rate location based on the Minister of Public Works and Public Housing No. 02 / PRT / M / 2016 on Improving the Quality of the Slum Housing and Slum (Anon. 2016). Then the pattern of treatment in improving the quality of slum area carried out in accordance with Law No. 1 of 2011 Article 97 (Anonymous, 2011), through (1) The restoration; (2) Rejuvenation; or (3) Resettlement. Handling practices followed by management to maintain the quality of housing and settlements. The research showed that (1) the area of Sindulang One Urban Village is one area of slums in the city of Manado with typologies / characteristics of settlements in the hills, plains and the waters edge (DAS Tondano and the waterfront) is based on the identification of the condition of untidiness, other considerations and the legality of land categorized as slum heavy that its existence is affecting the level of the city of Manado in general untidiness, therefore, this area can be prioritized to be one of the priority areas in the handling of the slums. The pattern of treatment that can be done to do that is the rejuvenation of the city with alternative land sharing to maximize the feasibility of the location to the fulfillment of environmental facilities and public facilities on land that is legal, and the land consolidation which is a pattern of development that is based on the wisdom of setting land ownership to improve the quality of life and maintenance resources natural as well as maximizing the strategic location of the region.